MAPPIX: A software package for off-line micro-pixe single particle aerosol analysis - CECCATO, DANIELE (Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms, 2009)
In the framework of a multiannual experiment performed at Baia Terra Nova, Antarctica, size-segregated aerosol samples were collected by using a 12-stage SDI impactor (Hillamo design). Approximately 2800 particles, belonging to the first four supermicrometric SDI stages – 8.39, 4.08, 2.68, 1.66 lm dynamic aerosol diameter cuts – were analyzed at the INFN-LNL micro-PIXE facility, a three lens Oxford Microprobe (OM) product, installed in the early nineties. Four regions on each of the 12 sub-samples were measured; 60 aerosol particles were detected on average in each of the analyzed regions. The off-line single aerosol particle (SAP) analysis of such big amount of data required software that is able to rapidly handle the acquired data, with a simple and fast area selection procedure; the subsequent automated PIXE spectra analysis with a specialized code was also needed. The MAPPIX 2.0 software was designed to make easier and faster the user jobs during the SAP analysis. The package is composed of two separate routines: the first one is devoted to data format conversion (OM-LMF file format to MAPPIX format), while the second one is devoted to micro-PIXE maps graphical presentation and aerosol particle selection procedure. The MAPPIX data format and software features will be discussed; a short report of the speed performances will be presented.